2007
DOI: 10.1242/jeb.003822
|View full text |Cite
|
Sign up to set email alerts
|

The vagus nerve mediates cardio-respiratory coupling that changes with metabolic demand in a temperate nototheniod fish

Abstract: -1 , respectively; P<0.05) but abolished all HRV and CRC, although M O 2 was significantly less for a given f H and f V compared to intact fish. Thus, P. angustata exhibits vagally mediated CRC, and the association between f H and f V varies according to oxygen demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Multi-strand Teflon-coated stainless steel wire (A-M Systems, USA), used for electrocardiogram (ECG) recording electrodes to measure f H , and an intraperitoneal catheter, used for drug delivery, were implanted as previously described (Campbell and Egginton, 2007;Campbell et al, 2006). The fish were allowed to recover in fresh aerated water then placed into a metabolic recording chamber, with the ECG leads exiting through the top of the chamber, and were not disturbed or fed for 96 h before initial readings were taken.…”
Section: Methodsmentioning
confidence: 99%
“…Multi-strand Teflon-coated stainless steel wire (A-M Systems, USA), used for electrocardiogram (ECG) recording electrodes to measure f H , and an intraperitoneal catheter, used for drug delivery, were implanted as previously described (Campbell and Egginton, 2007;Campbell et al, 2006). The fish were allowed to recover in fresh aerated water then placed into a metabolic recording chamber, with the ECG leads exiting through the top of the chamber, and were not disturbed or fed for 96 h before initial readings were taken.…”
Section: Methodsmentioning
confidence: 99%
“…The study proposed that if stimulation of the vagus nerve were to be repeated, before the last inhibition response ended then sustained inhibition may be maintained (Zagon and Kemeny 2000). Animal studies have shown cardiorespiratory coupling ceases after bilateral vagotomy, suggesting that cardiorespiratory synchronization is mediated by the vagus nerve, which imparts parasympathetic control (Campbell and Egginton 2007;Dick et al 2009;Topchiy et al 2011). In addition, schizophrenic patients exhibit decreased levels of cardiorespiratory synchronization, which indicates decreased vagal modulation and inhibition in the brainstem (Peupelmann et al 2009).…”
Section: Possible Role Of Membrane Potential In Cardiorespiratory Modmentioning
confidence: 99%
“…Unrestrained and normoxic fish exhibited long periods of CRS, which is under vagal control, as it can be abolished by cardiac vagotomy or injection of atropine (Taylor, 1992). Injection of neural tracers to identify VPNs (Axelsson et al, 1992); Antarctic fish 3, Paranotothenia angustata (Campbell and Egginton, 2007); sea bass, Dicentrarchus labrax (Iversen et al, 2010); skipjack tuna, Katsuwonus pelamis, and yellowfin tuna, Thunnus albacores (Keen et al, 1995); African lungfish, Protopterus annectens (Sandblom et al, 2010). Amphibians: axolotl, Ambystoma mexicanum ; African clawed toad, Xenopus laevis (Taylor and Ihmied, 1995); bullfrog, Lithobates catesbeianus (Taylor et al, 2012); pepper frog, Leptodactylus labyrinthicus (M.R.S., A.S.A.…”
Section: Chondrichthyes (Cartilaginous Fishes -The Elasmobranchs)mentioning
confidence: 99%